2022
DOI: 10.1080/21655979.2022.2084496
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression of hen egg white lysozyme with the assistance of xylanase fusion partner inPichia pastoris

Abstract: Due to its bacteriolytic activity, hen egg white lysozyme (HEWL) is widely used in the feed, food, and pharmaceutical industries. However, its application is hindered by low protein expression levels in microbial expression systems. In this work, a novel fusion protein expression strategy was proposed for increasing the expression level of HEWL. First, HEWL, fused with a highly expressed fusion protein partner xylanase XynCDBFV, is expressed in Pichia pastoris . Secondly, a linker includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…As fusion with xylanase XynCDBFV improves the protein expression of hen egg white lysozyme (HEWL), somatostatin and IGF‐1/LR3 IGF‐1, and the XynCDBFV‐somatostatin displays excellent antigenicity (Cui et al., 2022 ; Huang et al., 2021 ), we investigated whether xylanase could similarly enhance the expression level and antigenicity of SAG1. To test the hypothesis, the code optimized and synthesized SAG1 and XynCDBFV‐SAG1 gene sequences were inserted into the P. pastoris expression vector pPIC9K with the α‐factor leader sequence for recombinant proteins secretion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As fusion with xylanase XynCDBFV improves the protein expression of hen egg white lysozyme (HEWL), somatostatin and IGF‐1/LR3 IGF‐1, and the XynCDBFV‐somatostatin displays excellent antigenicity (Cui et al., 2022 ; Huang et al., 2021 ), we investigated whether xylanase could similarly enhance the expression level and antigenicity of SAG1. To test the hypothesis, the code optimized and synthesized SAG1 and XynCDBFV‐SAG1 gene sequences were inserted into the P. pastoris expression vector pPIC9K with the α‐factor leader sequence for recombinant proteins secretion.…”
Section: Resultsmentioning
confidence: 99%
“…XynCDBFV is a thermostable alkaline xylanase derived from a rumen fungus Neocallimastix patriciarum and highly recombinant expressed in P. pastoris (Fang et al., 2014 ; Han et al., 2017 ). Due to the high expression of XynCDBFV in P. pastoris , we have successfully fused it to several difficult‐to‐express proteins, such as somatostatin, HEWL and IGF‐1/LR3 IGF‐1, and these fusions greatly increased their expression levels in P. pastoris , while preserving their bioactivity (Cui et al., 2022 ; Huang et al., 2021 ; Lu et al., 2023 ). As shown in this study, fusion XynCDBFV with SAG1 did not increase the expression level of SAG1, but we found surprisingly that the fusion with XynCDBFV improved the immune protection of SAG1 against E. tenella , which is the first report that the fusion of xylanase with antigen improves the immune protection of antigen.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies have reported that some hen egg proteins can be successfully expressed using genetic engineering strategies. For instance, with the assistance of a xylanase fusion partner, hen egg-white lysozymes were recombinantly expressed in Pichia pastoris [ 71 ]. Therefore, a new research trend in the preparation of HEPs is genetic engineering strategies.…”
Section: Bioactive Peptides Derived From Hen Egg Proteinsmentioning
confidence: 99%